IN VIVO DETOXIFICATION OF ENDOTOXIN BY THE RETICULOENDOTHELIAL SYSTEM - Wiznitzer, T. (The Rockefeller University Press, 1960)
Evidence is presented that The normal RES extracts endotoxin from the circulation and inactivates it very rapidly. When the RES has been damaged, whether by a blockading agent, such as thorotrast, or by a reversible degree of hemorrhagic shock, it cannot extract more than a small per cent of the amount of the endotoxin the normal system can extract. Of that fraction of endotoxin which is extracted, very little is detoxified. An organ like the kidney, which does not contain a significant amount of RE tissue, does not extract more than an insignificant percentage of the injected amount, and therefore does not detoxify endotoxin. Since dephosphorylation is a process concurrent with detoxification, and does not occur in an organ which does not extract or inactivate a significant amount of injected endotoxin, it is probable that this process is an indirect index of detoxification. Within the time limits of these experiments, plasma alone does not inactivate endotoxin.